(3EOGQI GdGSJKeGQ (B:s (3Hjf GdfXQjI hGdJWHjb (B/s - (3YdhGf, bGSe fGjas ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2009)
(3bQGQGJ GdJNWjW ddGSJKeGQ, JbfjGJ GdeaGVdI Hjf GdGSJKeGQGJ, bQGQGJ GdGSJKeGQ, GdJMdjd GdCSGSj hGdJMdjd Gdafj ddGSJKeGQGJ, bQGQGJ Jehjd GdGSJKeGQ, bQGQGJ GdGSJKeGQGJ GdOhdjIs
(3HHdjhZQGajG(B: (3U(B.377(3; edGMb U(B.367s
Keywords: (3GdGSJKeGQs; (3GdJNWjWs